Interface Drainage and Antimicrobial Irrigation Avoid Repeat Keratoplasty for Post-DSAEK Cold Interface Abscess. Issue 9 (September 2021) - Yu, Angeli Christy; Myerscough, James; Socea, Sergiu; Furiosi, Luca; Spena, Rossella; Bovone, Cristina; Busin, Massimo
Abstract : Purpose: To describe a surgical technique for the diagnosis and treatment of post–Descemet stripping automated endothelial keratoplasty (DSAEK) infectious interface keratitis presenting as a cold abscess. Methods: This study included 2 eyes of 2 patients that developed delayed-onset interface infections after DSAEK. Through an anterior keratotomy, diagnostic samples for microbial culture and histopathology examination were collected, and empiric antibiotic therapy was delivered directly to the site of the infection at the graft–host interface. Results: In both cases, microbiological examinations confirmed a fungal etiology consistent with Candida. Resolution of infection was achieved, and no signs of posterior segment involvement or recurrence of infection were observed. Both corneas remained clear with final visual acuity of 20/25 and 20/32. No case required additional surgical intervention or repeat keratoplasty after more than 15 months of follow-up. Conclusions: Interface drainage with antimicrobial irrigation may be considered for the management of post-DSAEK interface infections presenting as a peripheral cold abscess. By avoiding intraocular seeding of infectious pathogens, the anterior approach can achieve clinical resolution of infection, maintain visual function, and preserve the DSAEK graft, thereby obviating the need for a therapeutic keratoplasty.